Injectable, dual cross-linkable polyphosphazene blend hydrogels - Potta, Thrimoorthy; Chun, ChangJu; Song, Soo-Chang (ELSEVIER SCI LTD, 2010)
A new class of injectable, self cross-linkable, and thermosensitive polyphosphazene-based blending systems of functional thiolated and acrylated polymers was designed and synthesized to develop an ideal injectable carrier, and to overcome many barriers associated with developing the injectable carriers, such as the uses of monomeric crosslinkers, catalysts, oxidants, pH adjustments, initiators, UV light, heat production and organic solvent. The aqueous solutions of the polymer blends were exhibited a solution state at low temperature, and transformed into a hydrogel state with desired mechanical strength at body temperature via thermosensitive hydrophobic interactions. The mechanical strength was further improved by the cross-linking of thiol groups with acrylate groups in the polymer network under physiological conditions. The thermoresponsive hydrophobic interactions in the polymer network accelerated the chemical cross-linking to improve the mechanical property. The mechanical strength, inner three-dimensional network, and degradation rate can be tuned through the degree of cross-linking between the thermosensitive and functional blended polymers. The results suggest that the self cross-linkable thermosensitive polyphosphazene blend systems have great potentials to play a crucial role as an injectable carrier because of their improved suitable mechanical properties for application potentials, in addition to their inherent advantages such as injectable, biodegradable and thermosensitive properties. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: CHITOSAN; COPOLYMERS; MEDICINE; DELIVERY; PROTEIN; GELS; PH